Factors influencing Nigerians to invest in sukuk for infrastructure development / Ibraheem Alani AbdulKareem, Mohd Sadad Mahmud and Muqaddam Oyetunji Ali - Oyetunji Ali, Muqaddam; Mahmud, Mohd Sadad; AbdulKareem, Ibraheem Alani (Universiti Teknologi MARA, 2021)
This study investigates the factors influencing the intention to invest in Sukuk towards infrastructural development in Nigeria. In this study, a quantitative research approach is used to obtained data through survey method and online questionnaires. Data were obtained in Abuja, the capital of Nigeria, from 163 investors and potential investors in Sukuk. The result showed that attitude, subjective norms, perceived behavioral control, and religiosity have a positive significant relationship with intention to invest in Sukuk. In addition, the finding of the study showed that the amount of information has a negative significant relationship with intention to invest in Sukuk. Therefore, the result of this study may help Sukuk issuers in identifying the factors that influence the intention to invest in Sukuk among the potential investors. This study contributes to the Islamic financial institutions by confirming the factors that may influence the intention of Nigerian to invest in Sukuk for infrastructural development.